Bullying in the Leading Schools of Mataram City: An Analysis of Issues and a Solution-Oriented Approach from an Islamic Law Perspective - Liswati Liswati; Saparudin Saparudin; Mohamad Iwan Fitriani (Madania: Jurnal Kajian Keislaman, 2024)
This study examines bullying in leading schools in Mataram City, focusing on its root causes and exploring solutions grounded in Islamic legal perspectives. Bullying significantly affects students’ mental and physical well-being, academic performance, and social development, underscoring the importance of fostering a safe, inclusive, and respectful learning environment. Employing a qualitative approach, the research integrates legal, sociocultural, and educational frameworks to analyze the persistence of bullying within the unique social and institutional dynamics of Mataram. The study emphasizes Islamic principles, including justice (adl), compassion (rahmah), and mutual respect (ta’awun), as foundational for addressing bullying. Practical strategies inspired by Islamic teachings, such as promoting care (tas’awun), enhancing positive interactions, and implementing preventive measures through school policies and religious education, are proposed. Community involvement, particularly the roles of parents, teachers, and religious leaders, is highlighted as essential for supporting student well-being. The findings suggest that integrating educational reforms with Islamic ethical values effectively combats bullying, ensuring both immediate intervention and long-term cultural shifts toward respect and harmony. This comprehensive framework, incorporating legal and cultural dimensions, aims to create nurturing educational environments aligned with justice and community welfare. Penelitian ini mengkaji fenomena perundungan di sekolah-sekolah unggulan di Kota Mataram dengan fokus pada penyebab utama dan solusi berbasis perspektif hukum Islam. Perundungan memiliki dampak signifikan terhadap kesejahteraan mental dan fisik siswa, prestasi akademik, serta perkembangan sosial, sehingga penting untuk menciptakan lingkungan belajar yang aman, inklusif, dan penuh penghormatan. Dengan pendekatan kualitatif, penelitian ini mengintegrasikan kerangka hukum, sosiokultural, dan pendidikan untuk menganalisis keberlanjutan perundungan dalam dinamika sosial dan kelembagaan khusus di Mataram. Penelitian ini menyoroti prinsip-prinsip Islam, seperti keadilan (adl), kasih sayang (rahmah), dan saling menghormati (ta’awun), sebagai landasan dalam menangani perundungan. Strategi praktis yang terinspirasi dari ajaran Islam, seperti mempromosikan kepedulian (tas’awun), meningkatkan interaksi positif, dan menerapkan langkah pencegahan melalui kebijakan sekolah dan pendidikan agama, diajukan sebagai solusi. Keterlibatan komunitas, khususnya peran orang tua, guru, dan tokoh agama, dipandang penting untuk mendukung kesejahteraan siswa. Temuan menunjukkan bahwa mengintegrasikan reformasi pendidikan dengan nilai-nilai etika Islam secara efektif dapat mengatasi perundungan, memastikan intervensi segera sekaligus perubahan budaya jangka panjang menuju penghormatan dan harmoni. Kerangka kerja yang komprehensif ini, yang menggabungkan dimensi hukum dan budaya, bertujuan menciptakan lingkungan pendidikan yang mendukung, selaras dengan keadilan dan kesejahteraan masyarakat.